2020
DOI: 10.1002/bmc.5048
|View full text |Cite
|
Sign up to set email alerts
|

Determination of amlodipine, indapamide and perindopril in human plasma by a novel LC–MS/MS method: Application to a bioequivalence study

Abstract: A robust and rapid UPLC–MS/MS method has been developed, optimized and validated for determination of amlodipine (AML), indapamide (IND) and perindopril (PRN) in human plasma. A positive electrospray ionization mode was used in a Xevo TQD LC–MS/MS instrument. A single sample preparation step using extraction technique was applied to extract the three analytes from plasma samples. There was no need to extract indapamide from blood samples in a further step. Extraction of the three drugs and internal standards w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Oral administration of S06593 (perindopril arginine salt 5 mg/indapamide 1.25 mg/amlodipine 5 mg) and S05590 (perindopril tert-butylamine salt 4 mg/ indapamide 1.25 mg) or amlodipine 5 mg in healthy Chinese volunteers led to similar mean plasma concentration-time profiles for perindopril, perindoprilat, indapamide and amlodipine. Another bioequivalence study has also shown no drug-drug interactions among perindopril, indapamide and amlodipine in healthy participants administered a FDC of perindopril/indapamide/ amlodipine [45].…”
Section: Acta Materia Medicamentioning
confidence: 98%
“…Oral administration of S06593 (perindopril arginine salt 5 mg/indapamide 1.25 mg/amlodipine 5 mg) and S05590 (perindopril tert-butylamine salt 4 mg/ indapamide 1.25 mg) or amlodipine 5 mg in healthy Chinese volunteers led to similar mean plasma concentration-time profiles for perindopril, perindoprilat, indapamide and amlodipine. Another bioequivalence study has also shown no drug-drug interactions among perindopril, indapamide and amlodipine in healthy participants administered a FDC of perindopril/indapamide/ amlodipine [45].…”
Section: Acta Materia Medicamentioning
confidence: 98%
“…It was observed that (i) there was poor recovery of Indp from plasma samples so it could be quantified only in blood samples in high concentrations [25,32,36] and not in plasma, and (ii) the new formulation containing three APIs (namely, amlodipine, Indp and perindopril) was being used for treatment of high blood pressure due to arterial hypertension [38]. Considering this literature, Rezk and Badr in 2020 [39] described quantitation of Indp in plasma collected from six batches of 26 Egyptian individual adult volunteers. Methyl t-butyl ether-dichloromethane-ethyl acetate (40:40:20, v/v) was used to extract the APIs by LLE approach in one step (with a recovery of >91%).…”
Section: Bioequivalence Study and Drug Screeningmentioning
confidence: 99%
“…1-a). Various analytical techniques have been reported for determination of AML, either alone or in combination with other drugs, including, spectrophotometric techniques (Attimarad et al 2019;Erden et al 2016;Hegazy et al 2015;Karadurmuş et al 2018;Khachornsakkul and Dungchai 2020;Mahant et al 2016;Saad et al 2016;Siridevi et al 2019), spectrofluorimetric techniques (Attala et al 2020;Dinç et al 2017;El-Kosasy et al 2015;Ibrahim et al 2015;Mabrouk et al 2018;Mohamed et al 2016;Mohammed 2015;Nasr and Shalan 2020;Sh Shalan et al 2015;Shereen Shalan and Nasr 2019), electrochemical techniques (Erden et al 2016;Wei et al 2016) and chromatographic techniques such as TLC-densitometry (Patel et al 2020a, b), LC-MS/ MS (Rezk and Badr 2020) and HPLC (Alaama et al 2015;Attimarad et al 2020;Desai et al 2019;Duraisamy and Jaganathan 2017;Ebeid et al 2015;Karadurmuş et al 2018;Mahant et al 2016;Nagamani et al 2020;Naik et al 2020;Patel et al Patel et al 2020a, b;Saleh et al 2020;Saputri et al 2018). Perindopril (PER), is an antihypertensive nonsulfhydryl angiotensin converting enzyme (ACE) inhibitor used to treat hypertension and stable coronary artery disease with nomenclature of (2S,3aS,7aS)-1-[(2S)-2-[[(2S)-1-ethoxy-1-oxopentan-2-yl]amino]propanoyl]-2,3,3a,4,5,6,7,7a-octahydroindole-2-carboxylic acid (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1-b). For determination of PER alone or in combination, a variety of analytical techniques have been reported including spectrophotometric techniques (El-Bagary et al 2016;Hegazy et al 2015;Karadurmuş et al 2018;Magdy et al 2018;Rahman et al 2017;Saad et al 2016;Siridevi et al 2019), spectrofluorimetric techniques (Al-Haj Sakur et al 2015Fael and Sakur 2015a, b;Sakur et al 2015) and chromatographic techniques including TLC-densitometry (Patel et al 2020a, b), LC-MS/MS (Rezk and Badr 2020) and HPLC (Duraisamy and Jaganathan 2017;Hassan et al 2020;Hemdan et al 2018;Karadurmuş et al 2018;Naik et al 2020;Patel et al 2020a, b;Saleh et al 2020).…”
Section: Introductionmentioning
confidence: 99%